Design Evaluation of Multi-Station Assembly Processes by Using State Space Approach - Shi, Jianjun; Ceglarek, Dariusz; Jin, Jionghua; Ding, Yu (My University, 2002)
This report considers the problem of evaluating and benchmarking process design configuration in a multi-station assembly process.